Linguistic Errors in Arabic Writing (Insya’) Among Students at SMAIT Al-Arabiyah Aceh Besar - Baihaqi, Baihaqi; Hayati , Salma; Rizki, Aulia (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
Maharah kitabah are one of the four core language skills in Arabic. To enhance writing proficiency in Arabic, this can be realized through the teaching of insya’.    Insya’ refers to the practice of Arabic writing by expressing ideas or thoughts in a structured form in accordance with Arabic grammatical rules.This study aims to analyze the linguistic errors made by students in Arabic writing skills, focusing on 11th-grade students at SMAIT Al-Arabiyah Aceh Besar. The most frequent errors identified were grammatical mistakes, particularly in the use of i‘rab and sharaf. In addition, vocabulary and spelling errors were also common among students. This analysis employs a linguistic approach to identify and classify the types of errors that occur. In this study, the researcher used a data collection technique in the form of a test. The test results were analyzed descriptively. The findings revealed several types of errors in students’ insya’, namely: nahwu errors, sharaf errors, language interference, and imla’ errors. Grammatical errors were found to be the most prevalent in students’ insya’ compared to other types of errors. These findings underscore the importance of strengthening students’ mastery of nahwu and sharaf in insya’ in order to minimize writing errors.